Hak Asasi Manusia Dalam Perspektif Hukum Internasional Dan Nasional - Nurcahyani, Dewita (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2024)
Human Rights (HAM) are fundamental rights universally possessed by every individual regardless of race, religion, or social status. In the perspective of international law, human rights are regulated through various instruments such as the 1948 Universal Declaration of Human Rights (UDHR) and other international agreements. Meanwhile, in the national context, human rights in Indonesia are guaranteed by the constitution and various legislations, including Law Number 39 of 1999 concerning Human Rights. This study aims to analyze the influence of international law on the implementation of human rights in Indonesia, focusing on the harmonization of national regulations with international principles. The method used is a qualitative-descriptive approach through literature review and analysis of legal documents. The findings show that although Indonesia has adopted various international instruments, challenges such as inconsistent law enforcement and lack of public awareness of human rights remain major obstacles. This research is expected to contribute to strengthening human rights protection at the national level through enhanced implementation and effective legal oversight.